Guitar boy - Auch, Mary Jane (Square Fish, 2012)
After his mother is severely injured in an accident and his father kicks him out of the house, thirteen-year-old Travis attempts to survive on his own until he meets a guitar maker and some musicians who take him in and help him regain his confidence so that he can try to patch his family back together.